Pneumococcal meningitis outbreak and associated factors in six districts of Brong Ahafo region, Ghana, 2016 - Timothy Letsa; Charles Lwanga Noora; George Khumalo Kuma; Ernest Asiedu; Gideon Kye-Duodu; Edwin Afari; Osei Afreh Kuffour; Joseph Opare; Kofi Mensah Nyarko; Donne Kofi Ameme; Emmanuel G. Bachan; Kofi Issah; et al. (BMC, 2018)
Abstract Background Meningitis, a disease of the Central Nervous System is described as inflammation of the covering of the brain and spinal cord (meninges). It is characterised by fever, severe headache, nausea, vomiting, stiff neck, photophobia, altered consciousness, convulsion/seizures and coma. In December, 2015, twelve suspected cases of meningitis were reported in Tain district in Brong Ahafo region (BAR). Subsequently, dozens of suspected cases were hospitalized in five district hospitals in BAR. We investigated to determine the magnitude, causative agent and risk factors for the disease transmission. Methods A community-based 1:2 case-control study (with 126 individuals) was conducted form 10/12/15 to 26/4/16 in 27 districts of Brong-Ahafo Region, Ghana. We defined suspected meningitis cases as people presenting with sudden headache and fevers (Temp> 38.0 °C) in combination with one of the following signs: neck stiffness, altered consciousness, convulsions, bulging fontanelle (infants) and other meningeal signs. Controls were selected from the same neighbourhood and defined as individuals with no overt meningitis signs/symptoms. We collected CSF samples and performed serological testing using Pastorex-Meningitis-Kit and culture for bacterial isolation. Moreover, structured questionnaires were used to collect data on socio-demographics, living conditions, health status and other risk factors. We conducted univariate data analysis and logistic regressions to study disease-exposure associations using Stata 15. Results A total of 969 suspected cases with 85 deaths (CFR = 9.0%) were recorded between December, 2015 and March, 2016. Majority, 55.9% (542/969) were females aged between 10 months-74 years (median 20 years, IQR; 14-34). Of the 969 cases, 141 were confirmed by Laboratory test with Streptococcus pneumoniae identified as the causative agent. Cases were reported in 20 districts but 6 of these districts reported cases above threshold levels. The outbreak peaked in week 6 with 178 cases. Overall attack rate (AR) was 235.0/100,000 population. District specific ARs were; Tain; 143.6/100,000, Wenchi; 110.0/100,000, Techiman; 46.6/100,000, Jaman North; 382.3/100,000 and Nkoranza South; 86.4/100,000. Female and male specific ARs were 251.3/100,000 and 214.5/100,000 respectively. Age group 10-19 years were most affected 33.8% (317/940). We identified sore throat [aOR = 5.2, 95% (CI 1.1-26.1)] and alcohol use [aOR = 9.1, 95%(CI 1.4-55.7)] as factors associated with the disease transmission. Conclusion Meningitis outbreak due to Streptococcus pneumoniae was established in BAR. Upper respiratory tract infection and alcohol use were associated with the outbreak. Mass campaigns on healthy living habits, signs and symptoms of meningitis as well as the need for early reporting were some of the control measures instituted. Moreover, we recommend Pneumococcal vaccination in BAR to prevent future outbreaks.